2011
DOI: 10.1177/0961203311412098
|View full text |Cite
|
Sign up to set email alerts
|

Using Wii Fit to reduce fatigue among African American women with systemic lupus erythematosus: A pilot study

Abstract: Fatigue and physical deconditioning are common, difficult to treat conditions among patients with systemic lupus erythematosus (SLE). The aim of this pilot study is to evaluate the effectiveness of a home-based exercise program using the Wii Fit system in patients with SLE. Fifteen sedentary African American women with SLE experiencing moderate to severe fatigue participated in a home exercise program using the Wii Fit 3 days a week for 30 minutes each for 10 weeks. A one-group pretest-posttest design was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 30 publications
6
90
2
3
Order By: Relevance
“…912, 17 Tench and colleagues randomized SLE patients to an exercise program, relaxation techniques, or no intervention. The patients in the exercise group were seen once every 2 weeks for a supervised exercise session and otherwise self-reported physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…912, 17 Tench and colleagues randomized SLE patients to an exercise program, relaxation techniques, or no intervention. The patients in the exercise group were seen once every 2 weeks for a supervised exercise session and otherwise self-reported physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of improved health outcomes following race-tailored interventions81 83 84 87 were similar to the reported acceptability and effectiveness of other culturally specific intervention programmes108 and consistent with studies that have suggested ways to neutralise, at least partially, the disadvantages of lower socioeconomic status associated with the excess morbidity and mortality in African-Americans with SLE 45109 110 These include:

improving access to quality healthcare;

targeting educational programmes to promote recognition and understanding of the disease and the comorbid conditions that affect outcome;

implementing programmes to improve self-monitoring and adherence to medical regimens;

developing opportunities to facilitate homemaking, childrearing and working outside the home;

applying psychosocial interventions to enhance self-confidence and social support.

…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have found that exercise can have substantial benefits for patients with inflammatory conditions, including but not limited to AS, [39][40][41]42,43 RA, 44,45 OA, 46 FM, 47 and IIM, 51-53 as well as CHF, 48 T2DM, 49 and metabolic syndrome, 50 which are considered low-grade systemic inflammatory diseases (Table 1).…”
Section: Practical Applicationsmentioning
confidence: 98%